Molecular cloning and designing transgenic vector carrying DAT gene isolated from Catharanthus roseus (L.) G. Don - Ha, Bui Thi; Tuong, Ho Manh; Hiep, Hoang Phu; Son, Le Van; Tam, Nguyen Thi; Mau, Chu Hoang (Academia Journal of Biology, 2015)
Catharanthus roseus (L.) G. Don is a dicotyledonous plant, which has the ability of producing some special alkaloids as vincristine and vinblastine that can cure cancers, especially blood cancer. Deacetylvindoline 4-O-acetyltransferase (DAT) is the catalyst key enzyme for the last reaction of vindoline biosynthetic process in Catharanthus roseus. Research on improvement of alkaloid content in periwinkle plants by approach of application of gene technology aims provide sufficient materials for medicinal purposes has been set out in the strategy of medicinal plant research in Vietnam. In this paper, we presented the results of cloning and determining the nucleotide sequencing of DAT gene (cDNA) isolated from mRNA of two varieties of Catharanthus roseus plant, viz. pink-purple flower variety (TN1) and white flower variety (TN2) that were collected at Thainguyen province. DAT gene isolated from two periwinkle sample TN1 and TN2 is 1320 nucleotides in length, encoding of acetyl CoA deacetylvindoline 4-O-acetyltransferase including 439 amino acids, participating in the last reaction chain of vindoline biosynthetic process. Comparative alignment of sequence of DAT gene between two sample TN1 (pink-purple flower) and TN2 (white flower) in Vietnam showed in 13 different location in nucleotide sequence of DAT gene. Sequence of deduced amino acid of two periwinkle samples TN1 and TN2 had 10 different location in amino acid sequence of DAT. Transgenic vector carrying DAT gene has been designed successfully. These results form the basis for generation of transgenic periwinkle plants overexpressing DAT, aiming to improve the alkaloid content in periwinkle plants.